Testing Structural Properties in Textual Data: Beyond Document Grammars. - F. Sasaki; J. Pönninghaus (Literary & Linguistic Computing, 2003)
Schema languages concentrate on grammatical constraints on document structures, i.e. hierarchical relations between elements in a tree-like structure. In this paper, we complement this concept with a methodology for defining and applying structural constraints from the perspective of a single element. These constraints can be used in addition to the existing constraints of a document grammar. There is no need to change the document grammar. Using a hierarchy of descriptions of such constraints allows for a classification of elements. These are important features for tasks such as visualizing, modelling, querying, and checking consistency in textual data. A document containing descriptions of such constraints we call a 'context specification document' (CSD). We describe the basic ideas of a CSD, its formal properties, the path language we are currently using, and related approaches. Then we show how to create and use a CSD. We give two example applications for a CSD. Modelling co-referential relations between textual units with a CSD can help to maintain consistency in textual data and to explore the linguistic properties of co-reference. In the area of textual, non-hierarchical annotation, several annotations can be held in one document and interrelated by the CSD. In the future we want to explore the relation and interaction between the underlying path language of the CSD and document grammars.